2016
DOI: 10.3389/fpsyt.2016.00020
|View full text |Cite
|
Sign up to set email alerts
|

Cortico-Cerebellar Connectivity in Autism Spectrum Disorder: What Do We Know So Far?

Abstract: Although the Autism Spectrum Disorder (ASD) is renowned to be a connectivity disorder and a condition characterized by cerebellar involvement, the connectivity between the cerebellum and other cortical brain regions is particularly underexamined. Indeed, converging evidence has recently suggested that the cerebellum could play a key role in the etiopathogenesis of ASD, since cerebellar anomalies have been consistently reported in ASD from the molecular to the behavioral level, and damage to the cerebellum earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 70 publications
2
42
0
3
Order By: Relevance
“…Indeed, in recent years there has been a surge in studies showcasing the cerebellum's role in attention (Baumann and Mattingley, 2014;Kellermann, et al, 2012;Striemer, et al, 2015). Genetic, animal model, post-mortem and neuroimaging studies, have all reported cerebellar differences between individuals with ADHD and those who are TD (Arime, et al, 2011;Baroni and Castellanos, 2015;Bonvicini, et al, 2016;Chess and Green, 2008;Rubia, et al, 2014;van der Meer, et al, 2016), as well as between TD individuals and those with ASD (for reviews see (Becker and Stoodley, 2013;Crippa, et al, 2016;Stoodley, 2016;Wang, et al, 2014). To our knowledge, however, this is only the second study to describe cerebellar FC with cortical networks in relation to attention or attention problems (see (Kucyi, et al, 2015) for an investigation into cerebellar FC with the DMN in relation to ADHD).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in recent years there has been a surge in studies showcasing the cerebellum's role in attention (Baumann and Mattingley, 2014;Kellermann, et al, 2012;Striemer, et al, 2015). Genetic, animal model, post-mortem and neuroimaging studies, have all reported cerebellar differences between individuals with ADHD and those who are TD (Arime, et al, 2011;Baroni and Castellanos, 2015;Bonvicini, et al, 2016;Chess and Green, 2008;Rubia, et al, 2014;van der Meer, et al, 2016), as well as between TD individuals and those with ASD (for reviews see (Becker and Stoodley, 2013;Crippa, et al, 2016;Stoodley, 2016;Wang, et al, 2014). To our knowledge, however, this is only the second study to describe cerebellar FC with cortical networks in relation to attention or attention problems (see (Kucyi, et al, 2015) for an investigation into cerebellar FC with the DMN in relation to ADHD).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has also been reported that children with ASD demonstrate diffusely decreased connectivity across the motor execution network relative to control children (Mostosky et al, 2009). This cortico-cerebellar connectivity dysfunction is also considered a core characteristic of ASD, and is thought to contribute to anomalies in both sensory-motor control, and higher function such as social cognition and emotion (Crippa et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…A recent MRI study has commented on the co-existence of Chiari malformation with some paediatric autism patients [267]. The targeting of the cerebellum by tretinoin is particularly relevant given that cerebellar abnormalities are a consistent feature of autism [268][269][270]. The transfer of retinoic acid across pig skin is increased by exposure to particulate matter containing polycyclic aromatic hydrocarbons [271].…”
Section: Cosmetic Ingredients Targeting Autism Genesmentioning
confidence: 99%